2020
DOI: 10.1021/acs.jpcc.0c05563
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Few-Layer Graphene Grown Vertically on a Cu Substrate via C60/Nitrogen Microwave Plasma and Its Field Emission Properties

Abstract: Vertical few-layer graphene (V-FLG) sheet is expected to be a high field emitter due to its electrical properties and open surface with sharp edges. However, the complicated and tedious preparation method using gaseous carbon-containing precursor limited the universal application of V-FLG. This paper reports a novel, simple, and green method to prepare vertical nitrogen-doped few-layer graphene (V-NFLG) on the metal surfaces that exhibit excellent field emission properties. The V-NFLG was grown on a Cu substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The growth of the 3-D NFLGs was carried out in a microwave excited C 60 /nitrogen plasma process, 29 as illustrated in Figure 1. Briefly, the process can be divided into three steps: (1) C 60 powder was heated by nitrogen plasma and evaporated into C 60 molecules; (2) the evaporated C 60 molecules were opened into C 2 and C−N molecules and flowed into the substrate surface with the nitrogen carrier gas; and (3) the C 2 and C−N molecules were adsorbed and transformed into 3-D NFLGs on a metal substrate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The growth of the 3-D NFLGs was carried out in a microwave excited C 60 /nitrogen plasma process, 29 as illustrated in Figure 1. Briefly, the process can be divided into three steps: (1) C 60 powder was heated by nitrogen plasma and evaporated into C 60 molecules; (2) the evaporated C 60 molecules were opened into C 2 and C−N molecules and flowed into the substrate surface with the nitrogen carrier gas; and (3) the C 2 and C−N molecules were adsorbed and transformed into 3-D NFLGs on a metal substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Heretofore, 3-D structured nitrogen-doped few-layer graphene sheets (3-D NFLGs) have been prepared using a fullerene C 60 precursor combined with a microwave excited nitrogen plasma process. 29 A deep understanding of the growth mechanism and available regulating of morphology for 3-D NFLGs is urgently needed, which is crucial for its widespread application. In this work, the detailed growth process of 3-D NFLGs, their structural characterization, and the field emission properties of the as-synthesized 3-D structural graphene sheets were studied.…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…is a common way to tune the electronic and mechanical properties of graphene, 13,14 thus improving carrier mobility and decreasing the work function. [15][16][17][18][19][20] Thus far, there have been a number of studies on N doping of graphene for the enhancement of field emission properties. Palnitkar et al prepared undoped and N-doped graphene by arc discharge method and found that the N-doped graphene exhibited a lower turn-on field of 0.6 V μm −1 compared to undoped graphene of 0.8 V μm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] Vortex beams can also acquire the azimuth information of the radar target, therefore benefiting the novel information‐rich radar for target recognition. [ 19 ] Recently, novel principles and inspiring applications of microwave vortices keep emerging, such as chirality detection, [ 20 ] spinning speed detection, [ 21,22 ] etc.…”
Section: Introductionmentioning
confidence: 99%